The Students' Perceptions of Bee Application in Learning Speaking at the Eleventh Graders - Yuniarti, Vyna; Dona, Dwi (CV. Doki Course and Training, 2025)
This study investigates the effectiveness of the Bee Application, a mobile-assisted language learning (MALL) tool, in enhancing speaking skills and engagement among the eleventh graders of 200 students at SMA Negeri 7 Prabumulih. The aim was to evaluate user satisfaction, usability, and improvements in speaking proficiency. A quantitative method with a survey approach was employed, utilizing data collected from questionnaires and total sampling method to provide a comprehensive analysis of the application’s impact. Results indicated a significant 30% improvement in students' speaking skills, with usability scores averaging 4.5 out of 5. Additionally, 75% of participants reported increased motivation to practice English, attributing their engagement to the application's interactive and gamified features. However, challenges such as technical issues and a desire for more diverse content were identified, necessitating further development. These findings underscore the positive effects of MALL applications on language acquisition. In conclusion, the Bee Application shows promise as an effective educational tool, and ongoing enhancements are recommended to address identified challenges and maximize its potential in language learning.